Synchrony Between Default-Mode and Sensorimotor Networks Facilitates Motor Function in Stroke Rehabilitation: A Pilot fMRI Study - Wu, Changwei W.; Lin, Shang-Hua N.; Hsu, Li-Ming; Yeh, Shih-Ching; Guu, Shiao-Fei; Lee, Si-Huei; Chen, Chun-Chuan (Frontiers in Neuroscience, 2020)
Stroke is the most common cause of complex disability in Taiwan. After stroke onset, persistent physical practice or exercise in the rehabilitation procedure re-organizes neural assembly for reducing motor deficits, known as neuroplasticity. Neuroimaging literature showed rehabilitative effects specific to the brain networks of sensorimotor network and default-mode network. However, whether between-network interactions facilitate the neuroplasticity after stroke rehabilitation remains mystery. Therefore, we conducted the longitudinal assessment protocol of stroke rehabilitation, including three types of clinical evaluations and two types of fMRI techniques (resting state and grasp task). Twelve chronic stroke patients completed the rehabilitation protocol for at least 24 hours and finished the three-time assessments: before, after rehabilitation and one month after the cessation of rehabilitation. For comparison, age-matched controls (n=12) underwent the same fMRI evaluation once without repeated measure. Increasing scores of Fugl-Meyer Assessment and Upper Extremity Performance Test reflected the enhanced motor performances after the stroke rehabilitation process. ANCOVA results showed that the connections between posterior cingulate cortex and iM1 persistently enhanced in contrast to the pre-rehabilitation condition. The interactions between posterior cingulate cortex and sensorimotor network were positively associated with motor performances. The enhanced cross-network connectivity facilitates the motor recovery after stroke rehabilitation, but the cross-network interaction was low before the rehabilitation process, similar to the level of normal controls. Our findings suggested that cross-network connectivity plays a facilitatory role following the stroke rehabilitation, which can be served as a neurorehabilitative biomarker for future intervention evaluations.